2019
DOI: 10.1108/maj-12-2018-2118
|View full text |Cite
|
Sign up to set email alerts
|

Auditing and credit granting to SMEs: an integrative perceptual model

Abstract: Purpose The purpose of this study is to develop an integrative model of credit granting to small- and medium-size enterprises (SMEs) incorporating the loan officers’ perceptual factors about SMEs (risk and trust) and accounting information (quality and usefulness). Moreover, the role of auditing on credit granting has been studied. Design/methodology/approach The structural equation modelling (SEM) approach is used to test the joint effect of explanatory variables. Empirical evidence is obtained from a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Empirical evidence suggests that the usefulness of information is a factor of perceived trustworthiness. It was further explained that people would generally trust companies that convey useful information (Palazuelos et al 2020). Easy access to information can demonstrate the importance of reliable information to build and maintain consumer trust (Najib et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Empirical evidence suggests that the usefulness of information is a factor of perceived trustworthiness. It was further explained that people would generally trust companies that convey useful information (Palazuelos et al 2020). Easy access to information can demonstrate the importance of reliable information to build and maintain consumer trust (Najib et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Research also suggests that less complex entities will select the nature of assurance (if any assurance) that best suits their circumstances (e.g., Gong et al, 2022;Palazuelos et al, 2020).…”
Section: N T Roductory Com M En Tsmentioning
confidence: 99%
“…Research also suggests that less complex entities will select the nature of assurance (if any assurance) that best suits their circumstances (e.g., Gong et al, 2022; Palazuelos et al, 2020). To the extent that entities may feel that the use of a standard for less complex entities miscommunicates the nature of the entity (e.g., somehow less sophisticated), entities will choose an audit undertaken with reference to the full suite of standards.…”
Section: Responses To Specific Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [17], many MSMEs around the world have significant financial needs but do not apply for credit. Several studies have found that firm characteristics, rather than industry factors, determine capital structure [18]. According to [19,20], small firms perceive debt as an expensive resource due to the costs of information asymmetry and credit services.…”
Section: Introductionmentioning
confidence: 99%